Knowledge and the social sciences : theory, method, practice - Goldblatt, David (David S.) (Introduction to the social sciences., 2004)
Knowledge and the Social Sciences: Theory, Method, Practice looks at the role of the social sciences in explaining and exploring what has been called the explosion of knowledge in the contemporary world.